2023
DOI: 10.36834/cmej.72758
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of journal clubs in undergraduate medicine

Abstract: Background: Training future doctors in the skills of evidence-based medicine (EBM) is clearly important. Journal club (JCs) are well-recognized educational interventions for teaching EBM. In contrast to postgraduate medical education, JCs use in undergraduate medical education (UME) has not been adequately explored. We conducted a realist review of the effectiveness of JCs in UME to unpack the underlying mechanisms by which the intervention works (or fails) in teaching EBM. Methods: The scope of review was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…A systematic review of the effectiveness of journal clubs in undergraduate medicine by Bello and Grant 17 evaluated which journal club educational interventions work in undergraduate medical education settings. Their review suggested that the journal clubs are a more effective tool when paired with lectures or mentoring.…”
Section: Reviews Theoretical Papers and Meta-analysesmentioning
confidence: 99%
“…A systematic review of the effectiveness of journal clubs in undergraduate medicine by Bello and Grant 17 evaluated which journal club educational interventions work in undergraduate medical education settings. Their review suggested that the journal clubs are a more effective tool when paired with lectures or mentoring.…”
Section: Reviews Theoretical Papers and Meta-analysesmentioning
confidence: 99%
“…Em adição, reconhece-se cada vez mais a importância da formação de futuros médicos nas competências e habilidades para uma Medicina Baseada em Evidências (MBE) (BELLO & GRANT, 2023;ARONSON, 2017). Trata-se de uma prática que permite a análise crítica das evidências presentes na literatura científica, visando aprimorar a qualidade nas tomadas de decisões e, consequentemente, o suporte oferecido aos pacientes (BELLO & GRANT, 2023;STRAUS et al, 2019).…”
Section: Introductionunclassified
“…Em adição, reconhece-se cada vez mais a importância da formação de futuros médicos nas competências e habilidades para uma Medicina Baseada em Evidências (MBE) (BELLO & GRANT, 2023;ARONSON, 2017). Trata-se de uma prática que permite a análise crítica das evidências presentes na literatura científica, visando aprimorar a qualidade nas tomadas de decisões e, consequentemente, o suporte oferecido aos pacientes (BELLO & GRANT, 2023;STRAUS et al, 2019). Nesse contexto, atividades de pesquisa científica quando introduzidas aos estudantes de medicina na graduação de maneira direcionada e organizada são consideradas um método que buscam melhorar resultados de aprendizados específicos atribuídos a aquisição e aumento de conhecimentos, além de, competências de redação e avaliação crítica dos novos conhecimentos com bases reflexivas (BELLO & GRANT, 2023;HARRIS, et al, 2011;NEL D, et al, FIGUEIREDO et al, 2021).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Health professionals also report the use of alternative methods to conduct their SDL such as journal clubs and interdepartmental communication tools [ 27 ]. Studies have confirmed journal clubs support, and are considered effective by learners, in their continued education [ 28 ] by facilitating knowledge gain and retention, skills of manuscript writing and critical appraisal. Recent research has found that professionals are utilizing specialized learning tools designed specifically to support learning and document management [ 29 ], such as Mendeley, Evernote [ 30 ] and more recently, Notion [ 31 ].…”
Section: Introductionmentioning
confidence: 99%